Antisite defects in nonstoichiometric Lu3Al5O12:Ce ceramic scintillators. Issue 9 (4th May 2015) - Hu, Chen; Liu, Shuping; Shi, Yun; Kou, Huamin; Li, Jiang; Pan, Yubai; Feng, Xiqi; Liu, Qian
<x xml:space="preserve">Abstract</x> Antisite defects (ADs) in nonstoichiometric Lu3Al5O12:Ce (LuAG:Ce) were studied systematically by a combination of first‐principles calculation based on density functional theory (DFT), X‐ray diffraction (XRD), and electron spin resonance (ESR) experiments. Calculations illustrated that LuAl, 16a AD is dominant in LuAG when an Lu2O3 excess exists. Nonstoichiometric LuAG:Ce ceramic with different Lu2O3 excess were prepared to verify the calculation results. The retrieved XRD lattice constants of Lu2O3 excess LuAG:Ce ceramics fit well with DFT calculation results on LuAl, 16a AD model, and the same distorted Ce sites in single crystals were also found in LuAG:Ce ceramics by ESR, which suggests the existence of LuAl, 16a ADs and they are dominant in nonstoichiometric LuAG:Ce ceramics, and thus measurable concentrations of ADs were detected in ceramics. This revealed that the formation of ADs is related to both temperature and chemical stoichiometry. LuAl, 16a antisite defects and nearest normal Lu sites.<inline-graphic xlink:href="ark:/27927/pgj2h39qtf0" content-type="pssb201451762-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />